2015
DOI: 10.4283/jmag.2015.20.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sintering Temperature on the Micro Strain and Magnetic Properties of Ni-Zn Nanoferrites

Abstract: In this study, nanocrystalline ferrite powders with the composition Ni 0.5 Zn 0.5 Fe 2 O 4 were prepared by the autocombustion method. The obtained powders were sintered at 800 o C, 900 o C and 1,000 o C for 4 h in air atmosphere. The as-prepared and the sintered powders were characterized by X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, and magnetization studies. An increase in the crystallite size and a slight decrease in the lattice constant with sintering temperature were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 29 publications
1
0
1
Order By: Relevance
“…Based on the Debye-Scherrer equation, shown in Table 2, the crystallite size of specimens decreased by the increasing sintering temperature from 900 to 1000 °C but increased homogenously at 1100 °C. This finding is different from the results of several previous studies, which revealed that the crystallite size increased with increasing sintering temperature with the same sintering temperature from 800 to 1000 °C [47,[49][50]. This anomalous behavior can be explained by assuming that a high defect concentration is produced during densification at 1000 °C; it can be attributed to the low crystallinity of the specimen at a sintering temperature of 1000 °C (Fig.…”
Section: X-ray Diffraction Investigationscontrasting
confidence: 96%
“…Based on the Debye-Scherrer equation, shown in Table 2, the crystallite size of specimens decreased by the increasing sintering temperature from 900 to 1000 °C but increased homogenously at 1100 °C. This finding is different from the results of several previous studies, which revealed that the crystallite size increased with increasing sintering temperature with the same sintering temperature from 800 to 1000 °C [47,[49][50]. This anomalous behavior can be explained by assuming that a high defect concentration is produced during densification at 1000 °C; it can be attributed to the low crystallinity of the specimen at a sintering temperature of 1000 °C (Fig.…”
Section: X-ray Diffraction Investigationscontrasting
confidence: 96%
“…4 shows the correlation between crystallite size and microstrain; the smaller crystallite size, the microstructure increases. This is corresponded by Venkatesh et al [39], reported that the decrease in the FWHM of the diffraction peaks with sintering temperature, indicating an improvement in the crystallization process by elimination of defects such as voids or vacancies, crystallite growth, and crystallite coalescence.…”
Section: Mineralogy and Crystallinitysupporting
confidence: 65%